Faktor-faktor yang Mempengaruhi Effective Tax Rate - Anna Nabhilla Husni; Joko Wahyudi (Universitas Sains dan Teknologi Komputer, 2022)
This study aims to examines and analyze the effect of firm size, leverage, profitability, capital intensity ratio, and independent commisioner on the effective tax rate. The population of this study were 42 mining companies listed on the Indonesia Stock Exchange in the 2017-2020 period, after using purposive sampling, 92 data observed were sampled. The data analysis method used is descriptive statistics, clasical assumptions, and multiple linear regression analysis processed with SPSS program. The results of this study are company size, leverage, profitability, and independent commisioner have a negative insignificant effect on Effective Tax Rate; and the Capital Intensity Ratio has a positive insignificant effect on the Effective Tax Rate.